9.
5/9 + 3/9 -4/9 = 4/9
4/6 + 2/6 -5/6 + 1/6= 2/6 = 1/3
8/8 -5/8 +1/8 + 2/8 = 6/8 = 3/4
10/10 - 5/10 - 2/10 + 6/10 = 9/10
8/10 - 6/10 +3/10 = 5/10 = 1/2
5/7 +1/7 -4/7 +2/7 = 4/7
10 .
7/8 - x = 4/8 x = 7/8 - 4/8 = 3/8
x-6/10 = 3/10 x = 3/10 + 6/10 = 9/10
4/6 + x = 9/6 x = 9/6 - 4/6 = 5/6
x - 7/10 =1/10 x = 1/10 + 7/10 = 8/10
9/9 + 3/9 - x = 6/9 12/9 - x = 6/9 x = 12/9 - 6/9 = 6/9
8/9 - x +3/9 = 4/9 11/9 - x = 4/9 x = 11/9 - 4/9 = 7/9
x + 4/8 -2/8 =5/8 x + 2/8 = 5/8 x = 5/8 - 2/8 = 3/8
8/6 - 4/6 -x =1/6 4/6 - x = 1/6 x = 4/6 - 16 = 3/6